Perancangan dan Implementasi Aplikasi Pengolahan Data Kematian Di Kantor Kelurahan Indralaya Mulia Ogan Ilir Menggunakan Vb.Net. - Sayuti, Akhmad; Krisna, Robi; Hendriansyah, Hendriansyah; Destikarini, Fartina (Journal of Information System and Education Development, 2025)
The design and implementation of a death data processing application at the Indralaya Village Office, Ogan Ilir Regency, aims to increase efficiency in managing death data. The manual data management process that is still often carried out today has the potential to cause various problems, such as data loss, input errors, and slow data search processes. This application was designed using Visual Basic .NET (VB.Net) as the main development platform, which was chosen for its ease of use and ability to create reliable desktop-based applications. The main functions of the application include inputting death data, archiving, searching for data, and creating reports. The system development method follows the SDLC (System Development Life Cycle) model with stages of requirements analysis, system design, implementation and testing. The database used is Microsoft Access to store death data in a structured and secure manner. The results of implementing this application show that the data management process has become faster, more accurate and organized. Apart from that, this application makes it easier for sub-district employees to compile regular death data reports. Thus, it is hoped that this application can be an effective solution in supporting administrative management at the Indralaya Village Office